Оброблення робочих поверхонь зубчастих коліс поверхнево-пластичним деформуванням - Паніна, Валерія Валеріївна; Панина, Валерия Валерьевна; Panina, Valeriia; Дашивець, Галина Іванівна; Дашивец, Галина Ивановна; Dashyvets, Halyna; Новик, Олексій Юлійович; Новик, Алексей Юльевич; Novyk, Oleksii (ТДАТУ, 2020)
UK: В статті розглядаються існуючі технології зміцнення поверхневого шару зубчастих коліс з застосуванням поверхнево-пластичної деформації. Основою вібраційного зміцнення є динамічний характер протікання процесу, що супроводжується безліччю мікроударів робочого інструмента або частинок робочого середовища по поверхні оброблюваних деталей. Обробка поверхнево-пластичним деформуванням з застосуванням вібраційних коливань обробного інструменту забезпечує поліпшення фізико-механічних властивостей оброблюваної поверхні. Це відбувається за рахунок циклічного впливу на деталь, що обробляється через робочий інструмент. Мікрорельєф, сформований віброобробкою, підвищує плавність роботи рухомого сполучення за рахунок зниження коефіцієнта тертя в 1,6 ... 2,2 рази. Створення регулярного мікрорельєфу на обох поверхнях пари тертя підвищує зносостійкість сполучення в середньому в 2 рази. RU: В статье рассматриваются существующие технологии упрочнения поверхностного слоя зубчатых колес с использованием поверхностной пластической деформации. Основой вибрационного упрочнения является динамичный характер прохождения процесса, что сопровождается бесконечными микроударами рабочего инструмента или частей рабочей среды по поверхности обрабатываемой детали. Обработка поверхностной пластической деформацией с использованием вибрационных колебаний обрабатываемого инструмента обеспечивает улучшение физико-механических свойств обрабатываемых поверхностей. Это происходит за счет цикличного воздействия на обрабатываемую деталь через рабочий инструмент. Микрорельеф, полученный вибронакаткой, повышает плавность работы подвижного соединения за счет снижения коэффициента трения в 1,6…2,2 раза. Создание регулярного микрорельефа на обоих поверхностях пары трения повышает износостойкость соединения в среднем в 2 раза. EN: Тhe article considers the existing technologies of strengthening the surface layer of gears with the use of surface-plastic deformation. In practice, surface hardening has developed and operates more than 130 different technologies. Damage to the economy of Ukraine can be caused by the use of economically inefficient processing methods due to limited information, as well as contradictions and opposite trends in the development of certain technologies. The current direction in technical service is surface hardening and drawing of strengthening coverings on gear wheels. The purpose of the article is to analyze the directions of development of surface hardening of gears, comparison of advantages and disadvantages of separate technologies, and also to estimate the most perspective decisions. The basis of vibration hardening is the dynamic nature of the process, accompanied by many micro-shocks of the working tool or particles of the working medium on the surface of the workpiece. This provides plastic deformation of the surface layer, which leads to increased microhardness, the formation of favorable compressive residual stresses and reduce surface roughness. Surface-plastic deformation treatment with the use of vibration oscillations of the processing tool improves the physical and mechanical properties of the treated surface. This is due to the cyclic effect of vibration on the part being machined through the work tool. As a result of vibration rolling, a significant increase in the service life of the transmission is achieved, which has a positive effect on saving money and time. The microrelief formed by vibration processing increases the smooth operation of the mobile connection by reducing the coefficient of friction by 1.6-2.2 times. When dry friction, the grooves work as traps that retain wear products, dust and abrasive particles, thus eliminating their abrasive effect. Creating a regular microrelief on both surfaces of the friction pair increases the wear resistance of the joint by an average of 2 times.
Обработка рабочих поверхностей зубчатых колес поверхностным пластическим деформированием
Processing of working surfaces of gear wheels by surface plastic deformation
Keywords: поверхневий шар; метод зміцнення; поверхнево-пластична деформація; мікрорельєф; вібронакатування; поверхностный слой; метод упрочнения; поверхностная пластическая деформация; микрорельеф; вибронакатка; surface layer; hardening method; surface-plastic deformation; microrelief; vibration rolling